Análise das relações entre parâmetros geolétricos e vazões para o aquífero livre de Caçapava do Sul - RS - Moreira, César Augusto [UNESP]; Cavalheiro, Mara Lia Dias; Pereira, Alice Marques [UNESP]; Sardinha, Diego de Sousa (Lepidus Tecnologia, 2013)
The geophysical methods may be employed in aquifer system studies, as determination of groundwater level, soil/rock contact, beyond estimative of the aquifer thickness horizon. The geoeletric methods are particularly relevant in evaluations of the oilfields systems, due to directs relations between porosity and electrical resistivity, which allow inferences about oil and gas production. The indirect estimative of the productions in free aquifers system is something complex before of the diverse variables responsible for factors or physical phenomena, as clays minerals, which conditioned the physical parameters by electric geophysical methods. This paper present analyzed correlation among electrical resistivity, chargeability and direct measure flow in shallow wells, for determination of statistical relationships between parameters and evaluation of the geological constraints evolved. The study count with the 23 shallow wells located in free aquifer, constituted by alteration materials of the granites localized in Caçapava do Sul (RS). The geophysical data are acquired by vertical electric sounding in Schlumberger array. The correlations between electrical resistivity and flow, chargeability and flow, thickness of the soil/saprolite and flow indicated relationships between physical and hydrogeologic parameters, with variations conditioned by factors as porosity, permeability, besides intrinsic geological heterogeneities such soil variable thickness and rock fragments with several alteration degrees.

Os métodos geofísicos podem ser empregados em estudos de sistemas aquíferos, como determinação da profundidade do nível aquífero, contato solo/rocha, além da estimativa de espessura de horizontes aquíferos. Os métodos geoelétricos são particularmente relevantes na avaliação de campos petrolíferos, devido a relações diretas entre porosidade e resistividade elétrica, que permitem inferências acerca da produção de óleo e gás. A estimativa indireta de produção em sistemas aquíferos rasos é algo complexo diante de diversas variá- veis responsáveis por fatores ou fenômenos físicos, como presença de argilominerais, que condicionam os parâmetros físicos medidos por métodos geofísicos elétricos. Este trabalho analisa correlações e ntre resistividade, cargabilidade e medidas diretas de vazão em poços rasos, para determinação de relações estatísticas entre parâmetros e avaliação dos condicionantes geológicos envolvidos. O estudo contou com 23 poços rasos locados num aquífero livre constituído por manto de alteração de granitos localizados no município de Caçapava do Sul (RS). Os dados geofísicos foram adquiridos por meio da técnica de sondagem elétrica vertical em arranjo Schlumberger. As correlações entre vazão e resistividade, vazão e cargabilidade, espessura da camada de solo/saprolito e vazão indicam relações entre propriedades físicas e hidrogeológicas, com variações entre os parâmetros condicionadas a fatores como porosidade, permeabilidade, além de heterogeneidades geológicas intrínsecas como espessura variável do solo e fragmentos de rocha com diversos graus de alteração.
Keywords: Geophysical; Free Aquifer; Statistical; DC Resistivity; Induced Polarization; Caçapava do Sul; Geofísica; Aquífero livre; Estatística; Eletrorresistividade; Polarização induzida; Caçapava do Sul - RS